Pengembangan Media Crossword Puzzle Berbasis Puzzle Maker sebagai Alat Evaluasi Siswa pada Materi Perubahan dan Pelestarian Lingkungan - Zakaria, Firda; Dama, Lilan; Hamidun, Marini Susanti; Nusantari, Elya; Husain, Ilyas H. (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop a Crossword Puzzle learning media based on the Puzzle Maker application as an evaluation tool for environmental change and conservation material in class X MAN 1 Boalemo. The background of this study is based on the low level of student involvement in biology learning which is still dominated by conventional methods, so that students have difficulty understanding abstract concepts. The research method used is Research and Development (R&D) with the Plomp development model which includes three stages, namely preliminary research, prototyping phase, and assessment phase. The subjects of this study were 22 students of class X MAN 1 Boalemo, and one biology teacher. The instruments used included expert validation questionnaires, student response questionnaires, teacher response questionnaires, and observation sheets for learning implementation. The results showed that the validity of the media was in the very valid category, with an assessment from material experts of 86% and a media expert of 96%. The practicality of the media was also assessed as very good based on the learning implementation reaching 93-95%, student responses with a percentage of 85%, and teacher responses of 93%. Thus, the Puzzle Maker-based Crossword Puzzle media is declared feasible and practical to use as an evaluation tool, and has the potential to increase student involvement in biology learning.